2019
DOI: 10.21273/horttech04442-19
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Photosynthetic Capacity of Basil Grown for Indoor Gardening under Constant or Increasing Daily Light Integrals

Abstract: In the quest to identify minimum daily light integrals (DLIs) that can sustain indoor gardening, we evaluated DLIs less than the recommended ranges for commercial production of basil (Ocimum basilicum). Experiments were conducted for 8 weeks to evaluate the effect of providing a constant vs. an increasing DLI over time (DLIInc) on growth and photosynthetic capacity of green (‘Genovese Compact’) and purple (‘Red Rubin’) basil grown hydroponically under a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…In general, all four of our investigated basil cultivars developed well under rising light intensity conditions which is in accordance with Solis-Toapanta and Gómez (2019) , who evaluated growths and photosynthetic capacities of green basil cultivar ‘Genovese Compact’ and purple cultivar ‘Red Rubin’ under increasing and constant light intensities.…”
Section: Resultssupporting
confidence: 88%
“…In general, all four of our investigated basil cultivars developed well under rising light intensity conditions which is in accordance with Solis-Toapanta and Gómez (2019) , who evaluated growths and photosynthetic capacities of green basil cultivar ‘Genovese Compact’ and purple cultivar ‘Red Rubin’ under increasing and constant light intensities.…”
Section: Resultssupporting
confidence: 88%
“…The DLI is an important environmental parameter for plants and displays stronger correlation with vegetative growth parameters than with photoperiod and light intensity [3,4]. Many studies have shown that a suitable DLI could promote the growth and development of plants, such as the germination rate of photoblastic seeds [5], shoot and root biomass [6][7][8][9], stem diameter [10,11], leaf area and leaf number [12], and the differentiation of flower buds [4,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…The application of PBZ reduced the stem diameter, with the smallest diameter (2.81 mm) being observed at the dose of 9.48 mg L -1 of PBZ. The number of leaves, leaf dry mass, stem dry mass and total dry mass were reduced to personal well-being and the home environment (Solis-Toapanta and Gómez, 2019). Plant growth regulators are chemical products commercially used in agriculture, mainly to adapt crops to commercial standards since they suppress growth without harming visual quality, do not promote phytotoxicity or thinning (Gazola et al, 2019).…”
Section: Resultsmentioning
confidence: 99%